PENGARUH CURRENT RATIO, RETURN ON ASSET DAN INFLASI TERHADAP HARGA SAHAM - Khairiyahtul Anwar; Soedjatmiko - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
Abstract, The purpose of this research is to determine whether the current ratio, return on assets and inflation affect stock prices in cosmetics and household appliances companies listed on the Indonesia Stock Exchange in 2011-2018. The population of this research is the Cosmetics and Household Goods company listed on the Indonesia Stock Exchange. Determination of sample size with non probability sampling technique with purposive sampling type. then the sample in this study were 4 companies The results of current ratio and inflation research have no effect on stock prices, while return on assets partially affect stock prices.